Nosocomial meningitis laboratory criteria in ICU patients: 5-year surveillance - N. V. Kurdyumova; D. Yu. Usachev; I. A. Savin; O. N. Ershova; O. A. Gadzhieva; M. A. Shifrin; G. V. Danilov; A. I. Burov (Вестник анестезиологии и реаниматологии, 2021)
Introduction. Nosocomial meningitis (NM) is one of the leading complications in neurosurgery due to high mortality and disability rates.Objective. The study was aimed to determine the reference values of laboratory parameters to diagnose NM in neurosurgical patients in the intensive care unit (ICU).Results. The incidence of NM in neurosurgical patients in ICU was 8.4 (95% CI 6.8–10. 0) per 100 patients. The dominant microbial agents of NM were coagulase-negative staphylococci, A. baumannii, and K. pneumoniae. We revealed the increase in leukocytosis, C-reactive protein, and blood procalcitonin in patients with infectious complications of other systems, regardless of NM presence. Episodes of hyponatremia and an increase in body temperature ≥ 38.0 occurred signifcantly more often in patients with NM. Changes in cerebrospinal ﬂuid (CSF) cytosis, glucose, lactate, and the CSF/blood glucose ratio can serve as reliable criteria in the NM diagnosis.Conclusions. The diagnosis of NM is most likely when the increase in CSF cytosis > 65 cells/μL, CSF lactate > 4.2 mmol/L is observed, the decrease in the CSF glucose < 2.6 mmol, and CSF/blood glucose ratio < 0.45 is found.